Decision making by health professionals during COVID-19: an integrative review - Camila Oliveira Valente; Fernanda Rios da Silva; Fernanda Carneiro Mussi; Maria Ribeiro Lacerda; Kátia Santana Freitas; Darci de Oliveira Santa Rosa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the scientific production on the decision making of health workers during the COVID-19 pandemic. Methods: Integrative review in the databases CINAHL, MEDLINE, Scopus, ScienceDirect, WoS, and BVS. Inclusion criteria: original articles available in full, in any language, related to the object investigated. Results: During this pandemic, health workers have been making decisions based on ethical/bioethical principles (utility, beneficence, non-maleficence, autonomy, justice, proportionality, flexibility, clinical prognosis, duration of the need, and fair health attention), values (solidarity, equality, equity, utilitarianism, relational autonomy, reliability, reciprocity, maximization of the benefits and resources, and prioritization of those in worse conditions), beliefs and personal motivation, protocols, directives, tools, algorithms, recommendations, and criteria. Final considerations: Decision making has never been so necessary as in this pandemic. This article is not a recipe for the professionals, since decision making is based on numerous factors. However, it provides them with a foundation that can be helpful in this difficult process.